2002
DOI: 10.1162/089892902317361930
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Sensory-Specific Cortex by Cross-Modal Stimuli

Abstract: Visual and auditory cortices traditionally have been considered to be "modality-specific." Thus, their activity has been thought to be unchanged by information in other sensory modalities. However, using functional magnetic resonance imaging (fMRI), the present experiments revealed that ongoing activity in the visual cortex could be modulated by auditory information and ongoing activity in the auditory cortex could be modulated by visual information. In both cases, this cross-modal modulation of activity took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
207
4
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(254 citation statements)
references
References 41 publications
40
207
4
2
Order By: Relevance
“…Model 2 explains deactivation as a consequence of cross-modal inhibition mechanisms that reduce potentially distracting neural processes (Laurienti, et al 2002). With respect to the present study, the Model 2 advocates that deactivation in the posterior insula, PCL, ACG, MTG, CG, PHG, PCG, and precuneus during WM but less so during VA is a result of direct neural inhibition.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Model 2 explains deactivation as a consequence of cross-modal inhibition mechanisms that reduce potentially distracting neural processes (Laurienti, et al 2002). With respect to the present study, the Model 2 advocates that deactivation in the posterior insula, PCL, ACG, MTG, CG, PHG, PCG, and precuneus during WM but less so during VA is a result of direct neural inhibition.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, fMRI studies using cross-modal stimuli showed deactivation of the auditory cortices during visual stimulation, while deactivation of the visual cortices occurred during auditory stimulation (Laurienti, et al 2002;Lewis, et al 2000). These findings suggest that the concomitant deactivation could represent cross-modal inhibition (an active suppression of neural activity), to minimize potentially distracting, taskirrelevant neural processes.…”
Section: Introductionmentioning
confidence: 75%
“…In reference to this deactivated area, Levitin & Menon (2003) reported greater activation in a similar region in the cuneus and superior and middle occipital gyri among other nearby areas in the presence of scrambled music compared to non-scrambled music. From this finding the authors did not infer this activation as reflecting processing of scrambled music, since many of these regions are known to be deactivated during both auditory and visual processing (Laurienti, Burdette, Wallace, Yen, Field, & Stein, 2002). In the study carried out by Alluri et al (2012), the left-right MTG (with leftward bias) seemed to be implicated in the perceptual processing of timbral features of the Piazzolla piece that was used in the present study.…”
Section: Neuroanatomy Of Working Memory For Musicmentioning
confidence: 61%
“…Task-related decreases in BOLD contrast (deactivations) have been reported in fMRI studies [14][15][16][17] and have been correlated with decreased blood oxygenation and neural suppression [17]. Functional neuroimaging studies could therefore provide the desired converging evidence by determining whether a stimulus category, such as faces, evokes spatially discrete BOLD contrast activations and deactivations.…”
Section: Introductionmentioning
confidence: 99%